2013
DOI: 10.1038/ncb2791
|View full text |Cite
|
Sign up to set email alerts
|

A Bcl-xL–Drp1 complex regulates synaptic vesicle membrane dynamics during endocytosis

Abstract: Following exocytosis, the rate of recovery of neurotransmitter release is determined by vesicle retrieval from the plasma membrane and by recruitment of vesicles from reserve pools within the synapse, the latter of which is dependent on mitochondrial ATP. The Bcl-2 family protein Bcl-xL, in addition to its role in cell death, regulates neurotransmitter release and recovery in part by increasing ATP availability from mitochondria. We now find, however, that, Bcl-xL directly regulates endocytotic vesicle retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 64 publications
(80 reference statements)
7
113
2
Order By: Relevance
“…In accordance with the previously mentioned findings, the cleaved Bcl-xL activity can be inhibited by ABT737 in a similar manner as we observed in our studies. 23 One interesting observation from our studies was that the selected cell lines have differential propensity to uptake exosomes. RPMI 8226 cells uptake exosomes at much higher rates compared with OPM2.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In accordance with the previously mentioned findings, the cleaved Bcl-xL activity can be inhibited by ABT737 in a similar manner as we observed in our studies. 23 One interesting observation from our studies was that the selected cell lines have differential propensity to uptake exosomes. RPMI 8226 cells uptake exosomes at much higher rates compared with OPM2.…”
Section: Discussionmentioning
confidence: 91%
“…In 2 different publications, it has been shown that Bcl-xL plays a role in membrane dynamics and synaptic vesicle uptake. 23,24 Li et al showed that the synaptic vesicle uptake is mediated by the interaction of Bcl-xL with Drp-1. 23 It would be interesting to investigate whether the same molecular complex mediates the uptake and endocytosis of exosomes by recipient cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCL-x L is an antiapoptotic protein with a role in the regulation of membrane dynamics and endocytosis. 27 DOCK8, a member of the evolutionarily conserved DOCK family proteins, 28 was shown to bind to nucleotide-free CDC42 to mediate the GTP-GDP exchange reaction. Thereby, CDC42 is spatially activated at the plasma membrane, 29 where it plays a crucial role in apical differentiation and BBM formation.…”
Section: Discussionmentioning
confidence: 99%
“…Because Drp1 physically interacts with Bcl-xL in neurons 24 and Bcl-xL inhibits autophagy through its binding to Beclin1, we investigated the involvement of Bcl-xL in the suppression of autophagy by Drp1. Using coimmunoprecipitation assays, we confirmed that Drp1 physically interacts with Bcl-2 and BclxL in cardiomyocytes in the presence of Drp1 overexpression (Online Figure IIIA).…”
Section: Circulation Researchmentioning
confidence: 99%